1994
DOI: 10.1021/bi00254a027
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Sites of Ribosome Bound Eukaryotic Elongation Factor 2 in 18S and 28S rRNA

Abstract: The involvement of ribosomal RNA in the binding of eukaryotic elongation factor eEF-2 to the ribosome was investigated. eEF-2 was complexed to empty reassociated 80S ribosomes in the presence of the nonhydrolyzable GTP analogue GuoPP[CH2]P. The formed complex was treated with dimethyl sulfate, 1-cyclohexyl-3-(2-morpholinoethyl)carbodiimide metho-p-toluenesulfonate, and micrococcus nuclease to allow specific modification at single-stranded regions of the rRNAs. The sites of modification were localized by primer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 65 publications
1
17
0
Order By: Relevance
“…Despite its apparent lack of CaM responsiveness, Clk1 was able to phosphorylate EF-2. Studies by others have indicated that hyperphosphorylation of EF-2 inhibits translation (63,64). Two other observations are at least consistent with a potential role for Clk1 in regulation of protein synthesis.…”
Section: Ca 2ϩmentioning
confidence: 56%
“…Despite its apparent lack of CaM responsiveness, Clk1 was able to phosphorylate EF-2. Studies by others have indicated that hyperphosphorylation of EF-2 inhibits translation (63,64). Two other observations are at least consistent with a potential role for Clk1 in regulation of protein synthesis.…”
Section: Ca 2ϩmentioning
confidence: 56%
“…This residue is also strictly conserved in other members of the translation-factor family (Bourne et al 1990(Bourne et al , 1991, which, together with the similarities in their structures and ribosome-binding modes (Dever et al 1987;Moazed et al 1988;Holmberg and Nygård 1994) suggests a common mechanism by which the ribosome activates GTP hydrolysis in all these proteins.…”
Section: Introductionmentioning
confidence: 77%
“…Moreover the ionic conditions are not identical in the two situations. It is clear that, in the cell, eEF-2 undergoes several other interactions with ribosomal proteins and rRNA [11,12]. The fact that we were unable to measure any interaction with eEF-2 when the P proteins were covalently linked to the sensor chip is possibly due to the fact that in the ribosome these proteins are flexible and at least partly mobile, as shown for their prokaryotic equivalents L7/L12 [13], whereas they were fixed on the sensor chip and could not move in our assay.…”
Section: Discussionmentioning
confidence: 99%